COHERENCE IN IELTS WRITING PRACTICE BY STUDENTS OF ENGLISH DEPARTMENT OF WIDYA GAMA MAHAKAM UNIVERSITY - Pane, Widi Syahtia (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
Coherence means the smoothness of sentences that are built within the paragraph or text. In this study the researcher wanted to reveal how is the coherence of IELTS writing practice text made by first semester students of Widya Gama Mahakam University. The researcher used qualitative as the study method and six steps of data analysis based on Creswell & Plano (2011). The coherence analysis utilized Oshima & Hogue (2006) theory which stated that there are 4 ways to create coherent paragraph; (1) using Transition Signals, (2) Using Consistent Pronouns, (3) Using Repeat of Keywords, and (4) Arrange the Ideas in Logical Order. The study reveals that all of students used seven types of Transition Signal, 50% students used consistent pronouns, all of the students used at least one repeated keyword from main idea during the paragraph and only 30% of the students Arrange the Ideas in Logical Order.